2022
DOI: 10.3390/pathogens11010095
|View full text |Cite
|
Sign up to set email alerts
|

HERV-K and HERV-H Env Proteins Induce a Humoral Response in Prostate Cancer Patients

Abstract: A higher expression of human endogenous retroviruses (HERVs) has been associated with several malignancies, including prostate cancer, implying a possible use as a diagnostic or prognostic cancer biomarker. For this reason, we examined the humoral response against different epitopes obtained from the envelope protein of HERV-K (HERV-K env-su19–37, HERV-K env-su109–126), HERV-H (HERV-H env-su229–241, HERV-H env387–399) and HERV-W (HERV-W env-su93–108, HERV-W env-su248–262) in the plasma of patients affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The role of HERVH as biomarker has been discussed in several cancers, including colorectal carcinoma, prostate cancer and lung cancer. 62 , 63 , 64 Further experiments, at the nucleic acid or protein level, are needed to verify whether HERVH is an effective diagnostic biomarker. HHLA2, a newly discovered immune checkpoint belonging to B7 family, is thought to be derived by HERVH.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HERVH as biomarker has been discussed in several cancers, including colorectal carcinoma, prostate cancer and lung cancer. 62 , 63 , 64 Further experiments, at the nucleic acid or protein level, are needed to verify whether HERVH is an effective diagnostic biomarker. HHLA2, a newly discovered immune checkpoint belonging to B7 family, is thought to be derived by HERVH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in contrast to antibodies against HERV-W, we observed a constant Abs response against HERV-K Env 19–37 that remains over time, up to 5 years of disease, and then decreases. HERV-K is probably not involved in the pathogenesis of T1DM but is related to a general HERV-K expression in other inflammatory conditions; however, this has to be confirmed [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of these is the HERV‐R/ env gene, whose transcriptional downregulation has been reported in cases of choriocarcinoma (Rote et al, 1998 ). In particular, significant antibody response was observed against HERVs envelope ( env ) epitopes detected in patients with diabetes and other diseases (Manca et al, 2022 ; Noli et al, 2021 ; Simula et al, 2021 ). In 2009, a study revealed that the presence of these env viral proteins could contribute to the development of cancer cells (Balada et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%